1972
DOI: 10.1172/jci106811
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Kinetics of Serum and Xanthoma Cholesterol Radioactivity in Patients with Hypercholesterolemia

Abstract: A B S T R A C T In four patients with hypercholesterolemia (type II hyperlipoproteinemia) and xanthomatosis the decay of serum cholesterol specific activity was followed for 53-63 wk after pulse labeling. Specific activity of biopsied xanthoma cholesterol was measured four times in the course of the study. The xanthoma specific activity curve crossed and thereafter remained above the serum specific activity curve. The average ratio of xanthoma to serum specific activity was 4.7 at the end of the study. The fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1973
1973
1985
1985

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…We believe that these findings suggest a net efflux of more richly labeled cholesterol from the shrinking adipose tissue mass; Samuel, Perl, Holtzman, Rochman, and Lieberman have also noted higher specific activities in this tissue than in plasma, after administering radioactive cholesterol intravenously, in a nonobese hypercholesterolemic patient (28).…”
Section: Discussionmentioning
confidence: 67%
“…We believe that these findings suggest a net efflux of more richly labeled cholesterol from the shrinking adipose tissue mass; Samuel, Perl, Holtzman, Rochman, and Lieberman have also noted higher specific activities in this tissue than in plasma, after administering radioactive cholesterol intravenously, in a nonobese hypercholesterolemic patient (28).…”
Section: Discussionmentioning
confidence: 67%
“…Clearly, with severe atherosclerosis and a very large pool of unlabeled cholesterol which would dilute greatly the entering labeled cholesterol, a longer time period would be required for equilibration. In other studies, when the lesions were less severe and the time periods longer, from 137 to 371 days, this crossover phenomenon of atheroma and plasma cholesterol sp act was demonstrated (3,5,7).…”
mentioning
confidence: 68%
“…Previous radioisotopic exchange studies in patients with limited life expectancy have indicated that the tracer cholesterol fed orally or administered intravenously could be detected in the aorta and other arteries at autopsy (2)(3)(4)(5)(6)(7). Since the labeled cholesterol was incorporated into the plasma lipoproteins after its administration (2,8), these results demonstrated a measure of equilibration of cholesterol between plasma and arterial tissues.…”
Section: Introductionmentioning
confidence: 81%
“…In 12 of the 17 patients a third exponential appeared after 25 wk, and probably reflected a third kinetic pool of more slowly exchangeable cholesterol. Samuel, Perl, Holtzman, Rochman, and Lieberman in another study also noted that if xanthomata were present, the specific activity of xanthoma cholesterol differed widely from plasma cholesterol specific activity and indicated that this cholesterol might constitute a fourth more slowly exchangeable kinetic pool (32) and might be a problem in patients with xanthomatosis. When the various kinetic parameters were derived by input-output analysis and compared with similar values obtained from analysis of 10-12-wk segments of the same curves, important quantitative differences between the short-term and long-term kinetic values were noted.…”
Section: Plasma Cholesterol and Cholestanol Concentrationsmentioning
confidence: 96%